2022
DOI: 10.33546/bnj.1746
|View full text |Cite
|
Sign up to set email alerts
|

Suicide prevention: A qualitative study with Thai secondary school students

Abstract: Background: Suicide is the second leading cause of death among adolescents around the globe. Therefore, understanding its causes and prevention is needed. Objective: This study aimed to explore Thai secondary school students’ perceptions related to causes and preventions of suicide and the learning needs of suicide prevention. Methods: A descriptive qualitative approach was employed in this study. Purposive sampling was used to select 32 adolescents for focus group discussions, and in-depth intervi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 15 publications
1
21
0
1
Order By: Relevance
“… Including youth with suicide ideation during development of a suicide intervention posed health concerns 31 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… Including youth with suicide ideation during development of a suicide intervention posed health concerns 31 …”
Section: Resultsmentioning
confidence: 99%
“…The CYP engagement score in research involving the design and/or implementation of health interventions ranged from 1-5. The majority of studies only reported engaging CYP during one (n = 13) 30,[32][33][34]37,38,44,[46][47][48][50][51][52][53][54] or two (n = 6) 29,31,35,[39][40][41] phases of the research process. Developing the research question and interpreting results had the lowest reported engagement of CYP, while designing methods had the highest reported engagement of CYP (Table 2).…”
Section: Presence Of Engagementmentioning
confidence: 99%
See 1 more Smart Citation
“…In this domain, we found 13 articles. Four of the included studies focused on programs implemented in schools (Breux & Boccio, 2019;Chaniang et al, 2019;Johnson & Parsons, 2012;Stein et al, 2010).…”
Section: Education Of Gatekeepersmentioning
confidence: 99%
“…As a result, school employees now serve as pupils' second parents. As a result, Saint Lucia school ought to offer mental health services and support mechanisms for students through behavior monitoring, direction, and counseling on stress management and how to react to physical behaviors and bullying [44]. To do this, it would be crucial to designate a few members of the school staff as mental health focal points or call points and teach them in the fundamental skills for spotting pupils who are most vulnerable to suicide behaviours [5].…”
Section: Implications For Research and Interventionmentioning
confidence: 99%